An assessment of readiness and willingness to adopt digital marketing transformation among SMEs’ entrepreneurs in Sabah: a conceptual model - Haslinda Hasan; Salmah Topimin; Siti Nor Baayah Ahmad; Irma Wani Othman (Academic Inspired Network, 2021)
Digital transformation is one of the most fundamental social and economic occurrences which impacts Small and Medium-sized enterprises (SME) business operations specifically during Covid-19 pandemic. The paper seeks to find out how digital marketing transformation impacts marketing activities in micro business entrepreneurs and to examine their readiness and willingness to adopt digital transformation after the pandemic by testing the theoretical framework based on the Image Theory. The results of this study will be based on a survey with micro business entrepreneurs located in Sabah which currently applying the digital transformation because of Covid-19 pandemic. This study will give implication to the industry players, decision makers and marketers in creating awareness activities to ensure the success of the digital marketing transformation to the SMEs in Sabah.